2018
DOI: 10.1186/s13046-018-0735-1
|View full text |Cite
|
Sign up to set email alerts
|

5′/ 3′ imbalance strategy to detect ALK fusion genes in circulating tumor RNA from patients with non-small cell lung cancer

Abstract: BackgroundDetecting an ALK fusion gene in patients with non-small cell lung cancer (NSCLC) could provide evidence to guide individualized therapy.MethodsThe 5′/3′ imbalance strategy for quantitative reverse transcription-PCR (RT-qPCR) was developed to detect ALK fusion genes in circulating tumor RNA (ctRNA) of NSCLC patients.ResultsThis method was validated in patients with the ALK fusion gene confirmed by next generation sequencing (NGS). The amount of the ALK fusion gene detected by the new method ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…The CHECKMATE [8][9][10] series of trials have suggested that a specific threshold of "tumour mutational burden" (TMB) must be reached in order for PD-1 blockade to become effective, although this has not been adopted formally, due to a lack of association between TMB and response, although other similar markers such as clonal TMB have shown promise. Although TMB has variable definitions, it is broadly accepted [9] as the number of missense mutations in the tumour genome, either divided by the size of the exome panel (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) or via the size of the human genome for whole-genome sequencing (WGS) (3.3 Gb). Based on the CHECKMATE trials, the suggested TMB threshold is greater than 10 mutations (mut)/Mb, based on the objective response rates of the tumours in these studies not improving much beyond this threshold.…”
Section: Introductionmentioning
confidence: 99%
“…The CHECKMATE [8][9][10] series of trials have suggested that a specific threshold of "tumour mutational burden" (TMB) must be reached in order for PD-1 blockade to become effective, although this has not been adopted formally, due to a lack of association between TMB and response, although other similar markers such as clonal TMB have shown promise. Although TMB has variable definitions, it is broadly accepted [9] as the number of missense mutations in the tumour genome, either divided by the size of the exome panel (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) or via the size of the human genome for whole-genome sequencing (WGS) (3.3 Gb). Based on the CHECKMATE trials, the suggested TMB threshold is greater than 10 mutations (mut)/Mb, based on the objective response rates of the tumours in these studies not improving much beyond this threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Other targetable mutations including ALK, BRAF, ROS1, MEK, and HER2 have been detected in plasma from patients with NSCLC, although the sensitivity for detecting these mutations is lower than that for EGFR mutant detection [15,[49][50][51][52]. The NGS-based approaches will facilitate detection of various rare genetic mutations that could be targeted.…”
Section: Future Perspectives On Circulating Tumor Dna Testing In Lungmentioning
confidence: 99%
“…Highly fragmented ctDNA could result in insufficient mappable sequences to identify fusion events [51]. New technologies have been developed for detection of ALK fusion in ctDNA or ctRNA [15,[49][50][51][52]. Recently developed, hybrid capture-based NGS can retrieve large genomic fragments to whole genomes with high sequencing coverage and accurate detection of genomic alterations, including genomic re-arrangements and short variants at low AFs and copy number amplifications.…”
Section: Future Perspectives On Circulating Tumor Dna Testing In Lungmentioning
confidence: 99%
“…We and others reported PCR tests, which utilize cDNA as a template and measure the amounts of 5′‐ and 3′‐end specific fragments of the involved tyrosine kinase 14‐16 . If the rearrangement occurs, the kinase domain of the involved gene is translocated to a highly expressed partner; therefore, the 3′‐end of the transcript is overrepresented as compared with the 5′‐end.…”
Section: Introductionmentioning
confidence: 99%
“…We and others reported PCR tests, which utilize cDNA as a template and measure the amounts of 5 ′ -and 3 ′ -end specific fragments of the involved tyrosine kinase. [14][15][16] If the rearrangement occurs, the kinase domain of the involved gene is translocated to a highly expressed partner; therefore, the 3 ′ -end of the transcript is overrepresented as compared with the 5 ′ -end. This test for unbalanced expression is potentially capable of detecting all variants of gene rearrangements, being similar in this respect to IHC and FISH.…”
Section: Introductionmentioning
confidence: 99%